Studi Kelayakan Perencanaan Pengembangan Kawasan Pendidikan di Kabupaten Majalengka berdasarkan Kriteria Smart Environment - Dewi Febriyanti; Hani Burhanudin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The concept design for the development of the education area in Majalengka Regency has been stated in the master plan document for the development of the Majalengka education area. Even though you already have a master plan, it is necessary to conduct a feasibility test of the plan before the plan is implemented to identify problems, opportunities, benefits and results that will be obtained from the plan. The suitability of the education area development plan with the smart environment criteria is an effort to realize environmentally sustainable development so as to reduce the chance of adverse impacts on the environment in the future. The purpose of this study was to analyze the feasibility level of implementing the development of an educational area in Majalengka Regency based on smart environment criteria so that recommendations were obtained. The method used in this research is descriptive quantitative by using scoring. Based on the results of the analysis, it shows that the education area development plan in Majalengka Regency is quite feasible to be implemented when viewed based on the smart environment criteria. Recommendations to expedite the implementation of this plan include facilitating licensing, making AMDAL, maximizing the socialization process to the community, adding aspects of disaster mitigation, implementing 5R concept waste management, adding a burial ground of at least 1 ha and developing environmentally friendly energy processing technology in planning documents and propose several programs or activities for environmental conservation such as reducing the use of paper and plastic. Abstrak. Rancangan konsep pengembangan kawasan pendidikan di Kabupaten Majalengka telah tertuang dalam dokumen masterplan pengembangan kawasan pendidikan Majalengka. Meskipun telah memiliki masterplan, perlu dilakukan uji kelayakan rencana sebelum rencana tersebut diimplementasikan untuk mengidentifikasi masalah, peluang, manfaat dan hasil yang akan diperoleh dari rencana tersebut. Kesesuaian rencana pengembangan kawasan pendidikan dengan kriteria smart environment merupakan suatu upaya dalam mewujudkan pembangunan berkelanjutan berwawasan lingkungan sehingga mengurangi peluang terjadinya dampak buruk bagi lingkungan di masa yang akan datang. Tujuan penelitian ini adalah menganalisis tingkat kelayakan implementasi pengembangan kawasan pendidikan di Kabupaten Majalengka berdasarkan kriteria smart environment sehingga didapatkan rekomendasi. Metode yang digunakan pada penelitian ini adalah kuantitatif deskriptif dengan menggunakan skoring. Berdasarkan hasil analisis, menunjukan bahwa rencana pengembangan kawasan pendidikan di Kabupaten Majalengka cukup layak untuk diimplementasikan jika dilihat berdasarkan kriteria smart environment. Rekomendasi guna melancarkan implementasi rencana ini diantaranya yaitu memudahkan perizinan, membuat AMDAL, memaksimalkan proses sosialisasi pada masyarakat, menambah aspek mitigasi bencana, menerapkan pengelolaan sampah berkonsep 5R, menambah tanah peruntukan pemakaman minimal 1 Ha dan pengembangan teknologi pengolahan energi yang ramah lingkungan pada dokumen perencanaan serta mengusulkan beberapa program atau kegiatan untuk pelestarian lingkungan seperti pengurangan penggunaan kertas dan plastik.